2019
DOI: 10.1186/s40497-019-0153-7
|View full text |Cite
|
Sign up to set email alerts
|

CEO characteristics and firm performance: focus on origin, education and ownership

Abstract: This study examines the impact of the chief executive officer's (CEO) ownership, education and origin on firm performance. The study uses balanced panel data for 6 years from 2011 to 2016 to run ordinary least square regression. Three variables that include the CEO origin, education and ownership are investigated in relation to firm performance. These characteristics are some of the basic CEO characteristics that are rarely considered by prior studies. The study uses a sample from firms in the financial sector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 53 publications
8
68
0
3
Order By: Relevance
“…The upper echelons theory also states that the background of the company leaders will affect how to view the internal and external problems and make decisions (Hambrick and Mason, 1984). Saidu (2019) and Wu et al (2011) described that the leaders who have a good education and strong experience will improve the high managerial skills present, so they will guarantee the company's sustainability. Frydman (2019) and King et al (2016) stated that having a background in business education can improve the managerial skill rather than technical skill.…”
Section: Ceo's Education and Cspmentioning
confidence: 99%
See 1 more Smart Citation
“…The upper echelons theory also states that the background of the company leaders will affect how to view the internal and external problems and make decisions (Hambrick and Mason, 1984). Saidu (2019) and Wu et al (2011) described that the leaders who have a good education and strong experience will improve the high managerial skills present, so they will guarantee the company's sustainability. Frydman (2019) and King et al (2016) stated that having a background in business education can improve the managerial skill rather than technical skill.…”
Section: Ceo's Education and Cspmentioning
confidence: 99%
“…A CEO with the higher level of education increases the prospect of the company's sustainability due to the increased capability to manage the company (Abernethy et al, 2019;Javakhadze et al, 2016;Kaur and Singh, 2019). Kokeno and Muturi (2016), Naseem et al (2019) and Saidu (2019) found that the CEO's education has a positive effect on the company's financial performance. Lewis et al (2014) and Tran and Pham (2020) also revealed that the CEO's education level has a positive effect on corporate environmental performance.…”
Section: Ceo's Education and Cspmentioning
confidence: 99%
“…Effective policies will have a positive impact on performance, both financial performance and social performance. Saidu (2019) and Darmadi (2013) have proven that CEO education has a significant influence on ROA. Thus, the following hypothesis can be developed:…”
Section: Introductionmentioning
confidence: 99%
“…Educational background is the basis of some researchers, i.e., Saidu (2019), Ayaba (2012), and Darmadi (2013), as an indicator that influences the effectiveness of managers in performing their duties. Previous studies show that education is important in corporate decision making and the outcome of these decisions is a reflection of CEO quality (Saidu, 2019). Manager education is the basis for assessing the knowledge and skills possessed by management (Cvilikas, Šarapovas, & Aurelijus, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation